PP-011 Impact of workload on preparations quality in chemotherapy: A pilot simulation study. (14th February 2016) - Carrez, L; Bouchoud, L; Fleury, S; Combescure, C; Falaschi, L; Bonnabry, P
Abstract : Background: Chemotherapy preparation units have to face increasing activity with constant staff. Safety is therefore threatened. Purpose: The purpose of our experiment was to measure the effect of work overload on preparation accuracy and error. Material and methods: A simulation study using tracers (lidocaine and phenylephrine) was conducted in an operational context. 12 operators had to produce 1, 2 or 3 sets of 8 preparations in a fixed time of 1 h. For each series of 8 preparations, 4 syringes at different dosages and volumes, starting from 2 concentrations of stock solutions, were compounded for each tracer. Results were analysed according to qualitative (visual observation, choice of stock solution, diluents and label) and quantitative (validated CE methods; accurate: <5% deviation from the target concentration; weakly accurate: 5–10%; inaccurate: 10–30%; error: >30%) criteria. Results: A gradual reduction in preparation time, inversely correlated with workload, was obtained (4 min 11 s, 3 min 07 s and 2 min 35 s for sessions with 8, 16 and 24 syringes, respectivelyp <0.0001). No difference in the accuracy of the doses was observed between the 3 levels of workload (p = 0.23, Cox model regression). The distribution of quantitative analysis for the production of 8, 16 and 24 syringes was as follows: accurate: 57%, 51% and 49%; weakly accurate: 26%, 25% and 32%; inaccurate: 16%, 23% and 17%; and error: 1%, 1% and 2%. The observed error rate (qualitative and quantitative analysis) for the preparation of 8, 16 and 24 syringes was 1.1%, 2.1% and 4.5%, respectively. The difference in errors rates between the 3 levels was not statistically significant (mixed effects logistic regression, p = 0.15), possibly due to a lack of power. Conclusion: Our pilot study showed that operators are able to increase their working speed without impacting on dose accuracy. However, a large proportion of inaccurate preparations were observed and inclusion of robust control methods in the process is recommended. Acceleration of the manual production rate appears to be possibly associated with a greater probability of making a mistake, but this trend has to be confirmed in a larger sample size study. No conflict of interest.